Modeling Liver Organogenesis by Recreating Three-Dimensional Collective Cell Migration: A Role for TGFβ Pathway - Ogoke, Ogechi; Yousef, Osama; Ott, Cortney; Kalinousky, Allison; Lin, Wayne; Shamul, Claire; Ross, Shatoni; Parashurama, Natesh (Frontiers in Bioengineering and Biotechnology, 2021)
Three dimensional (3D) collective cell migration (CCM) is critical for improving liver cell therapies, eliciting mechanisms of liver disease, and modeling human liver development and organogenesis. Mechanisms of CCM differ in 2D vs 3D systems, and existing models are limited to 2D or transwell-based systems, suggesting there is a need for improved 3D models of CCM. To recreate liver 3D CCM, we engineered in vitro 3D models based upon a morphogenetic transition that occurs during liver organogenesis, which occurs rapidly between E8.5 and E9.5 (mouse). During this morphogenetic transition, 3D CCM is characterized by co-migration (multiple cell types), thick strand interactions with surrounding septum transversum mesenchyme (STM), branching morphogenesis, and 3D interstitial migration. Here we engineer several 3D in vitro culture systems, each of which mimics one of these processes in vitro. In mixed spheroids bearing both liver cells and uniquely MRC-5 (fetal lung) fibroblasts, we observed evidence of co-migration, and a significant increase in length and number of liver spheroid protrusions, which was highly sensitive to transforming growth factor beta 1 TGFß1 stimulation. In MRC-5 conditioned medium (M-CM) experiments, we observed dose-dependent branching morphogenesis associated with an upregulation of Twist1, which was inhibited by a broad TGFß inhibitor. In models of in which liver spheroids and MRC-5 spheroids were co-cultured, we observed complex strand morphogenesis, whereby thin, linear, 3D liver cell strands attach to the MRC-5 spheroid, anchor, and thicken to form permanent and thick anchoring contacts between the two spheroids. In these spheroid co-culture models, we also observed spheroid fusion and strong evidence for interstitial migration. In conclusion, we present several novel cultivation systems that re-create distinct features of liver 3D CCM. These methodologies will greatly improve our molecular, cellular, and tissue-scale understanding of liver organogenesis, liver diseases like cancer, and liver cell therapy, and will also serve as a tool to bridge conventional 2D studies and preclinical in vivo studies.